Neutrophil to lymphocyte ratio is a prognosis factor for post-operative pneumonia in aneurysmal subarachnoid hemorrhage patients - Yue Chen; Bao-Qiang Lian; Lei Peng; Chen-Yu Ding; Yuan-Xiang Lin; Liang-Hong Yu; Deng-Liang Wang; De-Zhi Kang; Xiu-Yuan Hao (Chinese Medical Journal, 2021)
Abstract. Background:. Although a variety of risk factors of pneumonia after clipping or coiling of the aneurysm (post-operative pneumonia [POP]) in patients with aneurysmal subarachnoid hemorrhage (aSAH) have been studied, the predictive model of POP after aSAH has still not been well established. Thus, the aim of this study was to assess the feasibility of using admission neutrophil to lymphocyte ratio (NLR) to predict the occurrence of POP in aSAH patients. Methods:. We evaluated 711 aSAH patients who were enrolled in a prospective observational study and collected admission blood cell counts data. We analyzed available demographics and baseline variables for these patients and analyzed the correlation of these factors with POP using Cox regression. After screening out the prognosis-related factors, the predictive value of these factors for POP was further assessed. Results:. POP occurred in 219 patients (30.4%) in this cohort. Patients with POP had significantly higher NLR than those without (14.11 ± 8.90 vs. 8.80 ± 5.82, P < 0.001). Multivariate analysis revealed that NLR remained a significant factor independently associated with POP following aSAH after adjusting for possible confounding factors, including the age, World Federation of Neurosurgical Societies (WFNS) grade, endovascular treatment, and ventilator use. And the predictive value of NLR was significantly increased after WFNS grade was combined with NLR (NLR vs. WFNS grade × NLR, P = 0.011). Conclusions:. Regardless of good or poor WNFS grade, patients having NLR >10 had significantly worse POP survival rate than patients having NLR ≤10. NLR at admission might be helpful as a predictor of POP in aSAH patients.